Guyana : Recent Economic Developments. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1999)
This paper focuses on economic developments in Guyana during the 1990s. By 1991, economic performance had turned around in response to the shift in economic policies and the improved incentive framework. Following sizable reductions in 1989-90, real GDP grew by about 7 percent a year in 1991 and 1992, mainly owing to a recovery of export-related production and new foreign investments in the bauxite, gold, and forestry sectors. By 1992, inflation had declined markedly; the fiscal and external deficits were reduced substantially; and private and official capital inflows had risen significantly.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet